ANALYSIS THE INFLUENCE OF THE STYLE OF LEADERSHIP AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE AT SARANA LINTAS COMPANY IN SURABAYA - Waloyo, Waloyo (2021)
The purpose of present research was to asses the impact of the style of leadership and organizational culture on employee performance at the Sarana Lintas Company in Surabaya. The method used in this research is quantitative and explanatory survey methods. In present research, population was the entire staff employees with a total 120 people in Sarana Lintas Company and a random sample of 55 people was taken. Several linear regression analysis techniques are used as the data analysis technique in present research. The findings of present research show that the leadership style variable (X1) obtained a coefficient of 0.410, t-count 3.148, also a significance value of 0.003, while organizational culture variable (X2) obtained a coefficient of 0.532, t-count was 4.107, and a meaning value of 0.000, and a leadership style variable (X1) and a cultural organization (X2) obtained a count value F of 64.967 and a meaning value of 0.000. The present research concludes that there is a meaningful and positive impact on the style of leadership and organizational culture variables on employee performance at the company.